Ultrafast Nonlinear Optical Response of Low-Dimensional Semiconductors - Schäfer, Felix; Justus Liebig University Giessen (My University, 2024)
During this dissertation, an ultrafast spectroscopy laboratory featuring a high-repetition-rate regenerative amplifier built from the ground up. Additionally, an existing pump-probe setup was modified to enable ultrafast, polarization-dependent optical pump–optical probe spectroscopy experiments. The first setup has a repetition rate of up to 1 MHz and a central wavelength of 1030 nm, which was used to collect data for Paper I and the MoSe2 ML data for Paper III. The second system operates at a 5 kHz repetition rate system centered around 800 nm with a pulse shaper in the pump path to shape the excitation pulse to a FWHM of 2.71 meV, which was used for Paper II. Both setups employ an OPA to generate the excitation pump pulses tailored to the specific energy ranges required by the samples. An innovative measurement software routine was developed, utilizing a transfer function that reads out different ROIs of a CCD, simultaneously recording both the reference white-light and the transmitted light spectra through the sample. This approach allows the acquisition of the ∆αL signal with just one spectrum per time step, compared to the previous method, which required four spectra. A key advantage of this setup is that it eliminates the need for shuttering at each time step, accelerating measurements by a factor of two to three while effectively reducing global white-light fluctuations. The most time-intensive aspect of the measurement is now the precise positioning of the translation stage with sub-femtosecond accuracy and the acquisition of a spectrum. The stage can autonomously report its exact position to the measurement program, removing the need to wait for stage movement and allowing for continuous data acquisition. In this scenario, the primary speed-limiting factor becomes the CCD’s readout rate, which depends on the light intensity incident on the spectrometer to maintain an optimal signal-to-noise ratio. Paper I demonstrates that type-II semiconductor heterostructure systems can effectively serve as gain media in high-repetition-rate lasers. My study of the gain dynamics in model type-II systems reveals ultrafast gain recovery times, occurring within just a few picoseconds after a stimulated emission process. These findings establish the physical limit for the maximum repetition rate in laser systems based on (Ga,In)As/GaAs/Ga(As,Sb) type-II heterostructures. In practical applications, pulsed semiconductor laser sources utilizing type-II multi-quantum well structures could achieve repetition rates as high as 100 GHz, making them highly viable for advanced technologies. Paper II presents fundamental research on type-II heterostructures and their interaction with light. This study analyzes the microscopic mechanism driving the optical Stark effect in charge-transfer excitons within high-quality (Ga,In)As/GaAs/Ga(As,Sb) type-II heterostructures using a transient pump-probe measurement setup. The interaction between the CTX and the laser field was observed to depend on the polarization of the excitation and probe pulses. The blueshift of the CTX resonance, observed in both co- circular and counter-circular polarization configurations, contrasts with the shifts seen in spatially direct exciton resonances. Paper III will investigate experimental evidence of Rabi splitting in 1s exciton resonances in (Ga,In)As quantum wells and MoSe2 monolayers under resonant excitation conditions. Additionally, with increased excitation, I observed the emergence of additional absorption peaks, Rabi oscillations, and coherent gain in the MQW sample. This thesis opens new pathways for both fundamental research and technological applications in semiconductor physics. The demonstrated potential of type-II heterostructures as gain media in high-repetition-rate lasers indicates promising advancements in ultrafast optical communication. The optical Stark effect in charge-transfer excitons provides valuable insights into electron dynamics in semiconductors, paving the way for advancements in the design of more efficient electronic and optoelectronic devices. Furthermore, the observed Rabi splitting and coherent gain in quantum wells and TMDC monolayers highlight exciting opportunities in quantum information processing.
Keywords: Semiconductors; Heterostructures; Laser; Population inversion; Quantum wells; Ultrafast pump-probe spectroscopy; Stark effect; ddc:530